The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages and there seems to be a good case for the continuation of such bodies. Given a social security scheme, the workers in these organisations would be free from the routine financial problems met with to-day, and could do good work on the special ones. It might also be useful to have special centres for advice on marital difficulties, and in the immediate post-war period the problems arising out of demobilisation may necessitate special treatment, perhaps in centres set up for the purpose. It is a matter of controversy whether such service should be provided by voluntary organisations, or by the Government or Local Authorities. The Citizens' Advice Bureaux, which have done excellent service during the war, have been set up mainly by the National Council of Social Service, and have received valuable assistance from the staff and voluntary workers of such bodies as the Charity Organisation Society. At the same time Local Authorities have set up their own information bureaux, and in many localities the co-operation between the two has been very close. The question for the future is whether the Local Authorities should be encouraged to develop this branch of social service to the point where their bureaux become the principal local centres where social problems of all kinds may be brought, or whether such services should be the responsibility of national voluntary organisations. The many eminent and progressive persons who are in favour 21 15X/2/464/1